Analysis of Waters Physical Condition in Small Pelagic Fishing Location (Case Study at Fisheries Management Area (FMA) 715) - Angela Belladova Arundina; Projo Danoedoro; Muhammad Kamal (Green Publisher Indonesia, 2025)
The aim of research is to study the physical conditions at the small pelagic fishing locations relation with the ideal criteria for small pelagic fish habitat. In this research, physical parameters consist of temperature and chlorophyll-a will be analyzed according to conditions at the actual small pelagic fishing location in FMA 715 throughout 2018. The actual small pelagic fishing location is obtained from the fishing logbook data which is validated with the Vessel Monitoring System (VMS) data using Kernel Density Interpolation. Sea surface temperature (SST) and chlorophyll-a information at small pelagic fishing locations are extracted through MODIS Imagery. Small pelagic fish species at the fishing location are caught for Shortfin Scad, Trevally, Yellowstrip Scad, and Shadow Trevally. The results showed that the surface temperature at the small pelagic fishing location in FMA 715 is 21.56 - 31.75 oC and chlorophyll-a concentration is 0.08 - 1.33 mg/m3. It can be concluded that the physical conditions at the small pelagic fishing location are not always in accordance with the ideal habitat conditions. The conditions of sea surface temperature and chlorophyll-a that are close to the ideal conditions for small pelagic fish habitat are in the East Season.